2012
DOI: 10.1002/mrm.24538
|View full text |Cite
|
Sign up to set email alerts
|

Free‐Breathing 3D Cardiac MRI Using Iterative Image‐Based Respiratory Motion Correction

Abstract: Respiratory motion compensation using diaphragmatic navigator (NAV) gating with a 5 mm gating window is conventionally used for free-breathing cardiac MRI. Due to the narrow gating window, scan efficiency is low resulting in long scan times, especially for patients with irregular breathing patterns. In this work, a new retrospective motion compensation algorithm is presented to reduce the scan time for free-breathing cardiac MRI that increasing the gating window to 15 mm without compromising image quality. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…In this study, we have investigated the differences in respiratory patterns between a group of volunteers and patients with suspected or confirmed CAD. Consistent with earlier reports , we found that end‐exp is the most frequently occurring respiratory position at least in our sub‐group of healthy adult volunteers. However, the average respiratory pattern of our patient cohort included a higher frequency of intermediate respiratory positions located in‐between end‐exp and end‐insp (see Figure b,d).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we have investigated the differences in respiratory patterns between a group of volunteers and patients with suspected or confirmed CAD. Consistent with earlier reports , we found that end‐exp is the most frequently occurring respiratory position at least in our sub‐group of healthy adult volunteers. However, the average respiratory pattern of our patient cohort included a higher frequency of intermediate respiratory positions located in‐between end‐exp and end‐insp (see Figure b,d).…”
Section: Discussionsupporting
confidence: 93%
“…This particular SN implementation was successfully tested in both volunteers and patients . It has recently been established that end‐expiration (end‐exp) as a respiratory reference position in self‐navigated coronary MRA may be most promising in terms of image quality in healthy adult subjects with regular breathing patterns. However, in the case of more irregular respiration and respiratory drift as often occurring in patients , this may no longer apply and alternative strategies may thus be needed.…”
Section: Introductionmentioning
confidence: 99%
“…In case of radial kspace acquisitions, streak artifacts arise from azimuthal undersampling. To overcome these limitations, motioncompensated (MoCo) image reconstruction has been proposed (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). In contrast to gating, 100% of the measured data are employed for the reconstruction of each individual phase.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it was still dependent on the efficiency of the diaphragmatic navigator and its unpredictable scan time, which can severely drop in patients with irregular breathing patterns. Alternative motion compensation techniques, such as image-based navigation and selfnavigation (26)(27)(28), will be investigated in future studies to achieve 100% respiratory scan efficiency and consequently to further accelerate the scan, which can provide more comfort to the patient and reduce the risk of introducing additional bulk motion artifacts associated with long scans.…”
Section: The Phantom and Healthy Subjects' Retrospective Experiments mentioning
confidence: 99%